Comparative Study: Open Source Social Platforms (MOOCs) Arabic (Perception) and Foreign (Corcera) - Fraihat , Nesreen Bassam Fraid (Dirasat: Educational Sciences, 2020)
The current study aims to provide a comparison between the platforms and the ads of the source (in English) (in English) (in English). The results showed that the geographic location with a certificate in Arabic, with the location of Corsira, surpasses the number of printers used by the user following the Corsira platform in adopting this diversity and linking courses offered by the needs of Arab universities. The researcher also recommended the development of the sites so as to cover the negative aspects and support and develop the positive aspects. As well as financial support and emphasis on the need for electronic and technological infrastructure, which is the basis of providing and managing courses and education through the Internet and encourage educational institutions to benefit from electronic educational platforms through holding seminars and lectures to identify them and coordination and cooperation between educational institutions and state institutions, Teachers in educational institutions to contribute to the development of these courses within their field of study.